A voxel-based morphometry study on grey matter correlates of need for cognition and exploratory information seeking - Lau, Shermine Shimin (Nanyang Technological University, 2022)
Need for cognition (NFC) represents interindividual differences in tendencies to engage and enjoy cognitive endeavours. Exploratory information seeking (EIS) refers to individual tendencies to attain cognitive stimulation through acquiring information related to consumer products or services out of curiosity. Past research suggests that intrinsic motivation and curiosity seem to be the underlying conceptual mechanism driving an individual’s inclination to cognitive-related processes in NFC and EIS. Besides, research also suggests that both NFC and EIS are positively associated and centering around information-related behaviours. Consequently, the overlapping themes between NFC and EIS put forth the possibility that an individual’s level of NFC might directly influence their level of endorsement of EIS. The current study aims to provide an in-depth investigation of the relationship between NFC and EIS and extend this relation to determine neuroanatomical correlates of NFC and EIS. This study proposed two central hypotheses: (1) NFC and EIS scores will be positively correlated and (2) the grey matter volume (GMV) of brain regions implicated in motivation, valuation, and reward systems will be positively associated with both NFC and EIS. Self-report and structural MRI data of 91 Singaporean Chinese participants were utilized for the study. Correlational analysis and exploratory factor analysis indicated the absence of a relationship between NFC and EIS. Additionally, Voxel-Based Morphometry (VBM) whole-brain analysis revealed neuroanatomical correlates of the GMV of brain regions implicated in visuospatial, attentional and reward processing with NFC and EIS.